Comparison of radiological abnormalities between the jugular bulb and the vestibular aqueduct in patients with Ménière’s disease - Xia, Kaijun; Lei, Ping; Liu, Yingzhao; Li, Jing; Wang, Miao; Leng, Yangming; Liu, Bo (Frontiers in Neurology, 2023)
Anatomical variations of the inner ear may contribute to the development of Ménière's disease (MD), which is a complex inner ear disorder histopathologically characterized by idiopathic endolymphatic hydrops (ELH). Abnormalities of the vestibular aqueduct (VA) and the jugular bulb (JB) have been suggested as predisposing factors. Yet, few studies have investigated the correlation between JB abnormalities and VA variations as well as its clinical relevance in these patients. In this retrospective study, we investigated the differences in the incidence of radiological abnormalities of the VA and JB in patients with definite MD. Anatomical variations of JB and VA were evaluated based on high-resolution CT (HRCT) in a series of 103 patients with MD (93 unilateral cases and 10 bilateral cases). JB-related indices included JB anteroposterior and mediolateral diameter, JB height, JB type regarding to Manjila classification system, and incidences of JB diverticulum (JBD), JB related inner ear dehiscence (JBID), and inner ear adjacent JB (IAJB). VA-related indices included CT-VA visibility, CT-VA morphology (funnel, tubular, filiform, hollow, and obliterated-shaped type), and peri-VA pneumatization. Radiological indices were compared between MD ears and control ears. We found that radiological JB abnormalities were comparable between MD ears and control ears. As for VA-related indices, the CT-VA visibility was lower in MD ears than in control ears (p = 0.004). The distribution of CT-VA morphology was significantly different between MD and control ear (p = 0.013), with a higher proportion of obliterated-shaped type in MD ears (22.1%) than in control ears (6.6%). Compared with JB abnormalities, the anatomical variations of VA are more likely to be an anatomically predisposing factor for MD.